Validation study of the Narcissistic Personality Inventory-13 among a school sample of Portuguese youths - Pechorro, Pedro (2019)
The main aim of the present study was to translate and validate the Narcissistic Personality Inventory-13 (NPI-13) among a school sample (N=543) of male and female Portuguese youths. The NPI-13 demonstrated good psychometric properties, namely in terms of its three-factor structure, internal consistency, convergent validity, discriminant validity and criterion-related validity. Positive correlations were found with Conduct Disorder symptoms, alcohol use, drug use and unprotected sex. The psychometric properties of the NPI-13 mostly justify its use among Portuguese adolescents in a school context.